Pengaruh Pemasaran Digital dan Kualitas Sumber Daya Manusia Terhadap Pengembangan Umkm di Kabupaten Demak - Mochamad Hangga Novian (CiDEA Journal, 2022)
This research aims to examine the development of MSMEs in Demak Regency from a review of digital marketing and the quality of human resources. This research uses an explanatory method with a population of MSME actors in Demak Regency and a sample of 100 respondents. The results of the study show that: (1) There is an influence of digital marketing on the development of MSMEs in Demak Regency. (2) There is an influence on the quality of human resources on the development of MSMEs in Demak Regency. (3) There is an influence of digital marketing and the quality of human resources on the development of MSMEs in Demak Regency. The contribution of digital marketing and human resources variables to the development of MSMEs in Demak Regency is 66.40%, while 33.60% is influenced by other factors outside the research. Based on the results of this research, it can be concluded that digital marketing and the quality of human resources are important factors influencing the development of MSMEs in Demak Regency. Digital marketing can help MSMEs to reach a wider market and increase sales, while the quality of human resources can help MSMEs to develop innovative and quality products and services. Recommendations that can be given to improve MSME development in Demak Regency are: (1) The government and related agencies need to provide training and assistance to MSMEs to improve digital marketing capabilities and quality human resources. (2) MSMEs need to utilize digital technology to market their products and services. (3) MSMEs need to improve the quality of their products and services in order to compete in an increasingly competitive market